Sickle cell disease in children: chronic complications and search of predictive factors for adverse outcomes - Silva, IV; Reis, AF; Palaré, MJ; Ferrão, A; Rodrigues, T; Morais, A (Wiley, 2014)
BACKGROUND: Sickle cell disease (SCD) has extremely variable phenotypes, and several factors have been associated with the severity of the disease. OBJECTIVES: To analyze the chronic complications of SCD and look for predictive risk factors for increased severity and number of complications. METHODS: Retrospective study including all children followed for SCD in the Paediatric Haematology Unit of a tertiary hospital in Portugal, who completed 17 yr old between the years 2004 and 2013. RESULTS: We identified 44 patients, 55% female and 98% black. Chronic complications occurred in 80% of cases. Slight dilatation of the left ventricle was the most frequent complication (47.7%), followed by respiratory function disturbs (43.2%), microlithiasis or cholelithiasis (40.9%), increased flow velocity of cerebral arteries (31.8%), enuresis, delayed puberty and bone abnormalities (6.8% each), sickle cell retinopathy and leg ulcer (4.6% each) and recurrent priapism (2.3%). We identified a statistically significant association between leukocytes >15 000/μL and a higher number of hospitalizations (P < 0.001) and chronic complications of the disease (P = 0.035). The occurrence of dactylitis in first year of life was also significantly associated with a higher number of hospitalizations (P = 0.004) and chronic complications (P = 0.018). The presence of α-thalassemia was associated with a lower number of chronic complications (P = 0.036). CONCLUSIONS: Leucocytosis and dactylitis in the first year of life can be predictors of SCD severity, while the presence of α-thalassemia can be protective. The determination of early predictors of chronic complications of SCD may improve the comprehensive care of these patients.
Keywords: Criança; Anemia de Células Falciformes